1993
DOI: 10.1152/ajpcell.1993.264.3.c609
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of phospholipase D activity and phosphatidic acid production by norepinephrine in rat aorta

Abstract: We sought to relate norepinephrine (NE) stimulation of phosphatidic acid (PA) production to functional responses of rat aorta and pathways for PA production. The time course for changes in PA was closely related to Ca-dependent tonic responses in 42K efflux and contraction. NE (30 microM for 1 min) increased PA and reduced phosphatidylcholine (PC) and phosphatidylinositol (PI) based on Pi analyses and 32P labeling of phospholipids. The 32P-to-Pi ratio in PA (0.8 +/- 0.2, n = 13) was similar to PC (0.8 +/- 0.1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 21 publications
2
19
0
Order By: Relevance
“…The first evidence for such an effect was obtained in brain cortical slices in 1992 (26). The observation was then confirmed for various cell types and organs: isolated astrocytes (27), rat fibroblasts (28), rat tail artery (16), rat aorta (29), ventricular myocytes (30,31), and isolated perfused rat heart (32). Activation of PLD produces, besides choline, the second messengers phosphatidic acid and subsequently diacylglycerol (1 -3), both known to activate certain protein kinase Csubtypes.…”
Section: Activation Of Pldmentioning
confidence: 86%
“…The first evidence for such an effect was obtained in brain cortical slices in 1992 (26). The observation was then confirmed for various cell types and organs: isolated astrocytes (27), rat fibroblasts (28), rat tail artery (16), rat aorta (29), ventricular myocytes (30,31), and isolated perfused rat heart (32). Activation of PLD produces, besides choline, the second messengers phosphatidic acid and subsequently diacylglycerol (1 -3), both known to activate certain protein kinase Csubtypes.…”
Section: Activation Of Pldmentioning
confidence: 86%
“…The · 2A/D -receptor subtype has been suggested to mediate a portion of this vasoconstrictor response in at least some vessels, including the rat aorta [4]. Vascular · 2 -receptor responses have been shown to involve phospholipid hydrolysis in the absence of inositol trisphosphate formation [11], and studies in rat aorta have indicated that · 2A/D -receptor stimulation leads to PLD activation [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…The PLD pathway generates phosphatidic acid which can be converted into diacylglycerol by the action of phosphatidate phosphohydrolase, thereby providing PKC activation. In rat aorta studies, however, epinephrine-induced PLD activation was found to be sensitive to both the · 1 -receptor antagonist prazosin as well as the · 2 -receptor antagonist rauwolscine [5]. Since · 1 -receptors stimulate phosphoinositide hydrolysis in the rat aorta in association with the initial phase of contractile response [13], this observation raises the possibility that activation of PKC by · 1 -receptor costimulation might be important in allowing · 2 -receptor coupling to PLD.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations